Comparative analysis of diagnostic adequacy rate between aspiration and nonaspiration techniques of fine‐needle cytology in patients with thyroid cancer and ultrasonographically suspicious cervical lymph nodes. Issue 10 (18th August 2017) - Aydin, Cevdet; Dellal, Fatma Dilek; Tam, Abbas Ali; Ogmen, Berna; Kilicarslan, Aydan; Topaloglu, Oya; Ersoy, Reyhan; Cakir, Bekir
Abstract : Background: We aimed to compare nonaspiration (NAS) and aspiration (AS) techniques in the evaluation of fine‐needle cytology of lymph node (FNC‐LN) in terms of diagnostic adequacy of cytologic material. Methods: One hundred and twenty‐three superficial cervical LNs in 75 patients who underwent NAS and AS‐FNC‐LN in the same visit were evaluated. Cytological results were categorized as diagnostic and nondiagnostic. Results: The rates of malignancy were 13.8% in AS versus 16.3% in NAS technique, whereas nondiagnostic cytology was detected in 43.1% and 25.2%, respectively ( P  = .549 and P  < .01). Conclusions: The diagnostic adequacy rate in NAS‐FNC‐LN was significantly higher than AS‐FNC‐LN. However, NAS technique seems to be more simple and comfortable. We suggest both NAS and AS‐FNC‐LN in cytologic evaluation of suspicious cervical LNs until the diagnostic accuracy is determined with prospective studies.